Quality And Performance Analysis Of Drill Tools - Subramonian, Sivarao (2005)
The entire research identifies the unique characteristics of quality and performance analysis of twist drills. The drill tools with diameter of 10 mm made of high speed steel material were used for theentire research, as per the requirement of the sponsorer. The drills selected were geometrically identical, with same tool material but manufactured by two different manufacturers. The main aim of this scientific research is to find out, which manufacturers tool is better in quality and performance under the same combinations of cutting speed and feed.